The usage of modern radial diagnostic technologies in practical medicine - V. D. Zavadovskaya (Бюллетень сибирской медицины)
In the article the view of the scientific researches of the Department of radial diagnostic in SSMU is presented. Within the frames of the department interests besides the traditional researches in the fields of roentgenology there are such modern methods of medical visualization as search of new methods of osteoporosis-very developed and socially significant disease. The possibilities of usage the ultrasound for revealing the acute surgeon pathology of stomach and also for determination of criterias of activity of rheumatoid arthritis in knee-joint are studied. The new radioisotope methods of visualization of inflammatory processes of different localization are worked out. The possibilities of HRCT in the diagnostic of chronical obstructive diseases of lungs and obstructive bronchitis (COB) and bronchial asthma (BA) are researched. The intrusion of radial diagnostic methods for the determination of toxic influence of hepatite and drugs on the condition of parenchymatous organs existing in people who are drug addicts appears to be a new direction in work of the Department.